2007
DOI: 10.1021/jp075296a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Growth Mechanism of ZnO Nanowires by Selecting Catalysts

Abstract: The effect of catalysts on ZnO nanowire growth was investigated by comparing the performances of Au, Pt, and Ag nanoparticles. Additional control of growth was achieved by implementing a substrate temperature of either 800 °C with a ZnO/graphite powder source or 500 °C with a Zn powder source. At 800 °C, the vaporliquid-solid mechanism plays a very important role when the Au and Pt nanoparticles are in the liquid phase. On the other hand, nanowires can also be grown on solid nanoparticles, that is, oxidized Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 50 publications
4
96
0
Order By: Relevance
“…Firstly, the (002) peak intensity of ZnO nanostructures is significantly increased after step I compared with asdeposited film, then substantially increases after step II and step III. The growing mechanisms of formed well-arrayed ZnO nanostructures might include vapor-solid mechanism (VS) [8] and vapor-liquid-solid (VLS) mechanism [9], as described in our previous publication [7]. When the temperature increases, nuclear islands are quickly formed by the un-reacted zinc atoms on the surface of as-deposited thin film.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the (002) peak intensity of ZnO nanostructures is significantly increased after step I compared with asdeposited film, then substantially increases after step II and step III. The growing mechanisms of formed well-arrayed ZnO nanostructures might include vapor-solid mechanism (VS) [8] and vapor-liquid-solid (VLS) mechanism [9], as described in our previous publication [7]. When the temperature increases, nuclear islands are quickly formed by the un-reacted zinc atoms on the surface of as-deposited thin film.…”
Section: Resultsmentioning
confidence: 99%
“…Further study is needed for the knowledge of the process that is occurring in the vapor-solid process and of the role of Au/Pt nanoparticles in affecting the shape and size of ZnO particles, as well as their effectiveness in increasing quantities and homogeneity of the samples. Concerning the Pt-catalyzed growth of ZnO nanostructures, to the best of our knowledge, no systematic studies are reported and only two papers are shown on this subject [43,44]. …”
Section: Morphology From Sem and Afm Imagesmentioning
confidence: 99%
“…[6][7][8][9][10][11] The VPT process, in which Zn, 6,7 ZnO, 8 and a mixture of ZnO and carbon [9][10][11][12][13][14] are used as sources, has been the most frequently used for synthesizing a variety of ZnO nanostructures. For the carbothermal reduction using a mixture of ZnO and carbon powders, Zn vapors formed in the temperature range between 800 and 1200 o C are transported via a carrier gas onto a substrate and deposited as a thin film or nanostructures of ZnO on the substrate at lower temperatures.…”
Section: 2mentioning
confidence: 99%
“…The reaction temperature used in this study was lower than that [9][10][11][12][13][14] in the carbothermal reduction method. Zn vapor generated by the reduction of ZnO powder by CO at a hot zone is oxidized to ZnO vapor and then deposited on the substrate away from the crucible:…”
mentioning
confidence: 91%